IgG1 pan-neurofascin antibodies identify a severe yet treatable neuropathy with a high mortality - Fehmi, J; Davies, AJ; Walters, J; Lavin, T; Keh, R; Rossor, AM; Munteanu, T; Delanty, N; Roberts, R; Bäumer, D; Lennox, G; Rinaldi, S (BMJ Publishing Group, 2021)
Objectives We aimed to define the clinical and serological characteristics of pan-neurofascin antibody-positive patients. Methods We tested serum from patients with suspected immune-mediated neuropathies for antibodies directed against nodal/paranodal protein antigens using a live cell-based assay and solid-phase platform. The clinical and serological characteristics of antibody-positive and seronegative patients were then compared. Sera positive for pan-neurofascin were also tested against live myelinated human stem cell-derived sensory neurons for antibody binding. Results Eight patients with IgG1-subclass antibodies directed against both isoforms of the nodal/paranodal cell adhesion molecule neurofascin were identified. All developed rapidly progressive tetraplegia. Cranial nerve deficits (100% vs 26%), autonomic dysfunction (75% vs 13%) and respiratory involvement (88% vs 14%) were more common than in seronegative patients. Four patients died despite treatment with one or more modalities of standard immunotherapy (intravenous immunoglobulin, steroids and/or plasmapheresis), whereas the four patients who later went on to receive the B cell-depleting therapy rituximab then began to show progressive functional improvements within weeks, became seronegative and ultimately became functionally independent. Conclusions IgG1 pan-neurofascin antibodies define a very severe autoimmune neuropathy. We urgently recommend trials of targeted immunotherapy for this serologically classified patient group.